When the Hazard Is Human: Irrationality, Inequity, and Unintended Consequences in Federal Regulation of Contagion - Paula E. Berg (Washington University Law Quarterly, 1997)
This Article will take a critical look at OSHA and the CDC, which together constitute the federal system responsible for prospective regulation of the risk of contagion in institutional settings. In particular, this Article will argue that OSHA's recent inclusion in this regulatory system is highly problematic given the uneasy fit between the substantive and procedural provisions of the Act, geared as they are toward regulating hazardous things, and the task of regulating contagion arising from human beings. This Article will demonstrate that substantive and procedural provisions designed to regulate non-human phenomena by balancing two sets of rights, cannot be superimposed on a problem that requires the regulation of human beings and the balancing of multiple sets of rights without generating a panoply of theoretical distortions, regulatory irrationalities, and unintended consequences. The first section will provide an overview of the federal system for regulating contagion, and will describe and analyze the rulemaking process and the content of existing CDC and OSHA regulations. The second and third sections will examine the substantive and procedural provisions of the Act and the culture of OSHA, which together constrain the agency's ability to develop effective and equitable workplace contagion regulations. Finally, the last section will suggest how to reduce irrationality and inequity through reallocating authority to regulate contagion in institutions among the CDC, OSHA, and state public health officials and through OSHA's adherence to certain substantive principles and implementation of a number of procedural changes for regulation in this field.
Keywords: Communicable diseases; Industrial hygiene